Inovasi Pendidikan: Metode Pembelajaran Monoton ke Pembelajaran Variatif (Metode Ceramah Plus) - Satriani Satriani (Jurnal Ilmiah Iqra', 2016)
Education is the spearhead of a country. The more developed a country level will make the country more advanced. For that an educator should bias innovation in education. One of them by choosing teaching methods or create new methods appropriate to the learners so that the learning process can take place effectively and deliver results as expected. Teachers are required to have four competency in performing their duties. One of them is professional competence. For that, an educator must have the ability to keep abreast of the times. Today, the world is faced with rapid technological developments. Educators genius should be able to see it and take advantage of technology advances. However, the reality is the majority of educators can not develop their skills, especially regarding his duties as the subject of the learning process. Until finally learning activities becomes a difficult thing. This is evident from the number of educators both teachers and lecturers who use learning methods that are tedious (only one method such as a lecture).Keywords:educator, education, teaching methods and educational purposes.